Audit Committee Activities and the Internal Control System of Commercial Banks operating in Yemen - AL-Matari, Yahya Ali; Mohammed, Sulaiman Abdullah Saif; Al-Matari, Ebrahim Mohammed (International Review of Management and Marketing, 2017)
This study primarily aims to investigate the impact of audit committee effectiveness on the internal control system of commercial banks through the use of four of its characteristics namely audit committee meetings, meeting frequency between audit committee and internal auditors, audit committee reviews and internal audit proposals and lastly, audit committee reviews of the internal audit results. The study results were obtained by using data gathered from the Yemeni commercial banks through the questionnaire survey method. A total of 88 usable questionnaires out of 170 questionnaires distributed to 17 commercial banks were considered suitable for analysis. The results showed that the audit committee effectiveness, represented by meetings frequency between audit committee and internal auditors, audit committee reviews of the internal audit proposals, and audit reviews of the internal audit significantly related to the commercial banks performance. Literature regarding audit committee characteristics that are relevant to the present study was reviewed, and practical implications as well as recommendations for future studies were provided towards the end of the study. Keywords: Corporate governance, internal audit, audit committee, internal control system, Yemen. JEL Classifications: G34, M4